Trichoderma viride improves phosphorus uptake and the growth of Chloris virgata under phosphorus-deficient conditions - Song, Mingxia; Lin, Xiaoru; Wei, Xiaowei; Zeng, Qingpan; Mu, Chunsheng; Zhou, Xiaofu (Frontiers in Microbiology, 2024)
Phosphorus (P) deficiency can significantly impede plant growth. While Trichoderma viride (T. viride) has been recognized for promoting the assimilation of otherwise unobtainable nutrients, its impact on P uptake remains understudied. This research explored the influence of T. viride inoculation on P absorption and the growth of Chloris virgata (C. virgata) across various P sources. We treated plants with control P (P), tricalcium phosphate (TCP), calcium phytate (PHY), and low P (LP), with and without T. viride inoculation (P+T, TCP+T, PHY+T, LP+T). We analyzed photosynthesis parameters, growth indices, pigment accumulation, P content, leaf acid phosphatase activity. Results demonstrated that T. viride inoculation alleviated inhibition of photosynthesis, reduced leaf acid phosphatase activity, and enhanced growth of C. virgata in the presence of insoluble P sources. Additionally, T. viride inoculation enabled the plants to extract more available P from insoluble P sources, as evidenced by a substantial increase in P content: shoot P content surged by 58.23% to 59.08%, and root P content rose by 55.13% to 55.2%. Biomass P-use efficiency (PUE) declined by 38% upon inoculation with T. viride compared to the non-inoculated insoluble P sources, paralleled by a reduction in photosynthetic P-use efficiency (PPUE) by 26% to 29%. Inoculation under insoluble P sources further triggered a lower allocation to root biomass (25% to 26%) and a higher investment in shoot biomass (74% to 75%). However, its application under low P condition curtailed the growth of C. virgata. Our results suggest that T. viride inoculation represents an innovative approach for plants to acquire available P from insoluble P sources, thereby promoting growth amid environmental P limitations.